A New Approach to Design Artificial 3D Microniches with Combined Chemical, Topographical, and Rheological Cues. Issue 7 (23rd May 2018) - Stoecklin, Celine; Yue, Zhang; Chen, Wilhelm W.; de Mets, Richard; Fong, Eileen; Studer, Vincent; Viasnoff, Virgile
Abstract: The in vitro methods to recapitulate environmental cues around cells are usually optimized to test a specific property of the environment (biochemical nature or the stiffness of the extracellular matrix (ECM), or nanotopography) for its capability to induce defined cell behaviors (lineage commitment, migration). Approaches that combine different environmental cues in 3D to assess the biological response of cells to the spatial organization of different biophysical and biochemical cues are growingly being developed. It is demonstrated how the lamination of through‐hole polymeric biofunctionalized membranes can be implemented to create complex bona fide microniches with differential 3D environmental properties using photoactive materials. The approach enables to create microniches ranging in size from single cells to cell aggregates. They are biofunctionalized in 3D simultaneously with topographical featured, protein patterns and structured ECM surrogate with 1 µm resolution. It is demonstrated how these niches extend in 3D the ability to pattern cells. It is exemplified how they can be used to standardize cells' shapes in 3D and to trigger the apicobasal polarization of single epithelial cells. Abstract : An innovative platform for engineering three‐dimensional artificial microniches is presented. It allows to precisely and independently adjust the biochemical and physical cues from the single‐cell to organoid scale.